2021
DOI: 10.21744/lingcure.v5n1.1485
|View full text |Cite
|
Sign up to set email alerts
|

Identification of barriers and challenges to teaching English at an early age in Indonesia: an international publication analysis study

Abstract: This paper will identify some of the barriers and challenges in teaching English early in Indonesia. We believe that teaching English as a foreign language has many obstacles and challenges that must be raised and published so that all parties with interest in teaching foreign languages ??in Indonesia, especially in early childhood, will receive enlightenment. So, we have first received much input from various data sources that we access electronically. All of our data is related to the purpose of this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…It is in line with previous research findings that found teachers had a strong desire for the integration of ICT into education but they encountered many barriers (Malik et al, 2021). The major barriers were lack of confidence, lack of competence and lack of resources.…”
Section: Introductionsupporting
confidence: 91%
“…It is in line with previous research findings that found teachers had a strong desire for the integration of ICT into education but they encountered many barriers (Malik et al, 2021). The major barriers were lack of confidence, lack of competence and lack of resources.…”
Section: Introductionsupporting
confidence: 91%
“…Storytelling also plays a crucial role in improving English language skills such as listening, speaking, writing, and reading (Kristiawan et al, 2022). Due to learning English at an early age, means that children are given an opportunity starting to recognize different languages from the national to the world language (Malik et al, 2021). Therefore, choosing the storytelling method for the teaching and learning process is beneficial not only for early childhood but also for school-age children and adolescents.…”
Section: Storytelling Significance In Enhancing Children's Vocabularymentioning
confidence: 99%
“…threats to the speech partner and this category becomes the dominant category in the maxim of the speech form (Suryasa et al, 2019;Zavolzi, 2021). This means that speakers still follow the rules of polite politeness even though the discussion situation is in a formal situation and there are some debates between the presenter group and the discussion participants (Erbas et al, 2021;Malik et al, 2021).…”
Section: Question Of Student Omentioning
confidence: 99%